Aquifer Characterization and Modelling, a case study of Norne field. - Maganga, Sospeter Pastory (NTNU, 2017)
The purpose of this research is to characterize the Norne aquifer and testing its performance in the reservoir in terms of additional oil recovery factor with aquifer model included in reservoir simulation model by considering the use of Carter-Tracy model, Fetkovich model and van-Everdingen-Hurst (VEH) model. The methodology applied involves four stages: Aquifer characterization, model ranking aquifer modelling and economic analysis. The characteristics of the Norne aquifer considered are aquifer strength and aquifer properties such as aquifer size, aquifer permeability, aquifer porosity and water encroachment angle. The aquifer strength is determined by using diagnostic plots such as a production decline curve of oil rate versus time in semi-logarithm scale and drive indices plot. Estimation of aquifer properties is achieved by using a non-linear regression method in material balance software (MBAL). This approach involves history matching of the average reservoir pressure with computed pressure data by using production data, fluid injection rates and PVT properties. The computed pressure data from the tank model are history matched by regressing the most uncertain parameters in aquifer such as aquifer size, permeability, porosity, and water encroachment angle until the computed pressure matches with historical average reservoir pressure. In model ranking, three models are investigated. These are van-Everdingen-Hurst (VEH) model, Carter-Tracy model and Fetkovich model based on the standard deviation after regression analysis. In aquifer modelling, the Carter-Tracy model in Eclipse software is applied by using the estimated Norne aquifer properties. To introduce the Carter-Tracy aquifer in reservoir simulation model, three keywords are added in Eclipse data file. These are AQUDIMS for specifying dimensions for aquifer, AQUCT which specifies property data for Carter-Tracy aquifer and AQUANCON which specifies connection data for analytical aquifer. In economic analysis, total additional revenue is computed by ...